HOW “DIGITAL” IS THE NEW SERBIAN LAW ON DIGITAL ASSETS? - Motika, Zeljka (Pravni zapisi, 2022)
Papers focuses on the legislative changes from 2021 that the Law on Digital Assetsintroduced into the legal system of the Republic of Serbia and contextualizes the amendmentsfrom the perspective of existing practice. Introductory part evaluates the issue of whetherblockchain technology can secure trust and safety in the transactions that are executed viaInternet by parties from all over the world, as well as reasons that created the regulatoryframework for values that are transferred over distributed ledger technologiesinfrastructures. Main part of the paper examines in detail the legislative solutions within theLaw on Digital Assets as well as key exceptions and terms and their impact on the localeconomy. The section is followed by an overview of the draft legislation in EU in the field aswell as how it may impact Serbian economy as a third country. Aside from concludingremarks on legislative changes domestically, the paper outlines potential upcomingchallenges related to blockchain and instruments that may require a different approach inregulation.
Keywords: digital assets; ICO; White Paper; tokens; blockchain